The Role of Zinc in the Pathophysiology and Treatment of Depressive Disorders: A Literature Review - Przygoda, Aleksandra; Skowron, Aleksandra; Orzeł, Jakub; Pelczar, Patrycja (Quality in Sport, 2026)
Background. Depression is one of the most common mental disorders worldwide and represents a major public health concern. Increasing evidence suggests that dietary factors, including trace elements such as zinc, may play a role in the development and course of depressive disorders. Zinc is involved in numerous biological processes within the central nervous system, including neurotransmission, neuroplasticity, immune regulation, and oxidative balance. Aim. The aim of this study was to review the current literature on the role of zinc in the pathophysiology and treatment of depressive disorders, with particular emphasis on underlying biological mechanisms, clinical findings, and potential therapeutic implications. Material and methods. The studies cited in the presented review were selected from Pubmed and Google Scholar. The search included studies between 2020 and 2026. The key words used for the search included: depression; zinc; zinc deficiency; zinc supplementation Results. The available literature indicates that zinc deficiency is frequently observed in patients with depression and is associated with greater severity of symptoms. Experimental and clinical studies suggest that zinc influences key mechanisms implicated in depression, including NMDA receptor modulation, regulation of brain-derived neurotrophic factor (BDNF), dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, and inflammatory processes. Furthermore, zinc supplementation may enhance the efficacy of antidepressant therapy and improve clinical outcomes, particularly when used as an adjunctive treatment. Conclusions. Zinc appears to play a significant role in the pathophysiology of depression and may represent a promising target for adjunctive therapeutic strategies. However, further well-designed randomized controlled trials are required to establish optimal supplementation protocols and to better define the clinical applicability of zinc in depressive disorders.